Carbapenemase-Producing Enterobacteriaceae in Transplanted Patients. (4th October 2017) - Sukiennik, Teresa; Branco, Daniela; Stadnik, Claudio; Scheibler, Aline; Galo, Luciana
Abstract: Background: The carbapenemase-producing enterobacteriaceae (CPE) dissemination among transplanted patients is increasing and with difficult control, worries infection preventionists, because these infections treatment are extremely difficult, leading to high mortality rates.. The aim of this paper is to describe the CPE incidence density in transplanted patients and epidemiological profile in this group. Methods: Retrospective descriptive study between 2016 and February 2017, in transplanted patients from a tertiary hospital. Results: There were 166 positive cases for CPE, with an incidence density 5.34 per 1, 000 patient-days. Of these patients, 83 (50%) kidney, 50 (30.1%) hepatic, 20 (23%) pulmonary, 11 (6.6%) hematopoietic stem cell (HSCT), and 2 (1.2%) conjugated kidney and livers, being 104 males (62.7%). Among the genes identified were 162 bla KPC (97.6%), 3 NDM (1.8%), and 1 OXA48 (0.6%). Majority of these cases were colonization (88%) and detected by rectal swab (84.9%). Among the clinical samples, 15 (60%) urine, 5 (20%) respiratory, and 3 (12%) blood. The overall mortality rate was 13.9% (23), but infections 40% (08). Mortality in transplanted patients was 8 (9, 6%) kidney, 7 (14%) hepatic, 7 (35%) pulmonary, and 1 (9.1%) HSCT. The germs identified were: 145 (87.3 %) Klebsiella pneumoniae, 6 (3.6%) Enterobacter sp., 6 (3.6%) Serratia sp., 5 (3.0%) Citrobacter sp., and 4 (2.4%) others. Conclusion: The results show a high mortality rate, as well as widespread dissemination among transplant patients. Due to the high number of colonized individuals, it is necessary to maintain epidemiological surveillance with a strategy for the prevention of cross-transmissions and monitoring CPE incidence in a hospital environment. Disclosures: All authors: No reported disclosures.